The Impact of Marriage Dispensation Policy Interventions on Underage Marriage Trends Among Banyuwangi Teenagers - Yumna, Hanin (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
The phenomenon of underage marriage in Banyuwangi Regency is a crucial issue that shows an alarming trend even though the minimum age of marriage has been increased. This study aims to examine the impact of the marriage dispensation policy intervention implemented by the Banyuwangi Regency Government in an effort to reduce the number of underage marriages that occur among teenagers. This research uses a qualitative method with an analytical descriptive approach that collects data through observation, interviews and documentation and the data analysis was carried out using the reduction, presentation, and conclusion stages. The results showed that policy intervention through the signing of a Memorandum of Understanding (MoU) between the local government and Banyuwangi Religious Court, which requires recommendations for psychological maturity and reproductive health checks for marriage dispensation applicants, has had a positive impact. There has been a decrease in the number of marriage dispensation applications granted since September 2024. The policy has also strengthened the objective basis for judges in deciding cases and encouraged a shift in society's perspective on the importance of marriage readiness. However, the implementation of this policy still faces challenges related to the influence of religious and traditional leaders. Therefore, the recommendation to involve religious and customary leaders in education is considered important to align the policy with local values and achieve long-term effectiveness in preventing underage marriage. [Fenomena pernikahan di bawah umur di Kabupaten Banyuwangi merupakan isu krusial yang menunjukkan tren mengkhawatirkan meskipun batas minimum usia pernikahan telah ditingkatkan. Penelitian ini bertujuan mengkaji dampak intervensi kebijakan dispensasi nikah yang diterapkan oleh Pemerintah Kabupaten Banyuwangi dalam upaya menekan angka pernikahan di bawah umur yang terjadi di kalangan remaja. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif analitis yang mengumpulkan data mealui observasi, wawancara, dan dokumentasi serta analisis data dilakukan menggunakan tahap reduksi, penyajian, dan kesimpulan. Hasil penelitian menunjukkan bahwa intervensi kebijakan melalui penandatanganan Nota Kesepahaman (MoU) antara pemerintah Daerah dan Pengadilan Agama Banyuwangi, yang mensyaratkan rekomendasi kematangan psikologis dan pemeriksaan kesehatan reproduksi bagi pemohon dispensasi nikah, telah memberikan dampak positif. Terdapat penurunan jumlah permohonan dispensasi nikah yang dikabulkan sejak September 2024. Kebijakan ini juga memperkuat dasar objektif bagi hakim dalam memutuskan perkara serta mendorong pergeseran cara pandang masyarakat tentang pentingnya kesiapan menikah. Meskipun demikian, implementasi kebijakan ini masih menghadapi tantangan terkait pengaruh tokoh agama dan adat. Oleh karena itu, rekomendasi melibatkan tokoh agama dan adat dalam edukasi dianggap penting untuk menyelaraskan kebijakan dengan nilai lokal serta mencapai efektivitas jangka panjang dalam pencegahan pernikahan di bawah umur.]